1982
DOI: 10.1136/jnnp.45.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of therapeutic exercise on masticatory function in patients with progressive muscular dystrophy.

Abstract: SUMMARY The slope of the curve relating integrated electromyographic activity of masseter muscle to biting force, the latency of the jaw-jerk reflex, and masticatory performance were estimated in patients with Duchenne type of progressive muscular dystrophy before and during therapeutic exercise of the somatognathic system. The slope and latency were slightly decreased, and masticatory performance was increased during exercise. These results suggest that therapeutic exercise of the stomatognathic system is eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1986
1986
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Kawazoe et al . (1982) studied the effects of isometric exercise on the masticatory function in patients with progressive muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Kawazoe et al . (1982) studied the effects of isometric exercise on the masticatory function in patients with progressive muscular dystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…For masticatory muscles, two studies showed that jaw and tongue training for 24 weeks, accompanied by massage of the masseter muscle, could improve jaw performance and ease of eating [99, 100] (Table 2B). …”
Section: Experimental Procedures For Exercise In Patients With Dmdmentioning
confidence: 99%
“…The indication for orthodontic treatment to improve masticatory function is difficult to determine as progressive development of the dentofacial abnormalities in MD renders prognosis unpredictable. The inability of the masticatory muscles (as well as other skeletal muscles) to relax after voluntary contraction in myotonic dystrophy patients has been reported 49 . Clinically, this will present as a rigid jaw with limitation in opening if the masseter muscle is involved.…”
Section: Oral Health Considerationsmentioning
confidence: 99%